2015
DOI: 10.1136/bcr-2015-210228
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoparathyroidism in pregnancy

Abstract: SUMMARYHypoparathyroidism is an uncommon endocrine deficiency characterised by low serum calcium, absent or inappropriately low parathyroid hormone and normal or high serum phosphorus levels. Parathyroid hormone is essential for calcium homoeostasis. Pregnancy and lactation are known for increased calcium requirement. They cause calcium stress as well as alter its metabolism. Hence, many abnormalities are expected in hypoparathyroidism during pregnancy and lactation. We report a case of pregnancy in postsurgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…In contrast to these reports of improved or stable calcium metabolism, other reports have found that hypoparathyroidism significantly worsens during pregnancy: serum calcium falls, hypocalcemic symptoms may or may not increase, and the doses of supplemental calcium and vitamin D, 1␣-hydroxyvitamin D, or calcitriol have been increased (96,141,148,411,434,510,517,600,669,790,796,821,837,884,936). In one woman the endogenous calcitriol level was low at mid-pregnancy, but measurements in the third trimester were not reported (510).…”
Section: Human Datamentioning
confidence: 49%
“…In contrast to these reports of improved or stable calcium metabolism, other reports have found that hypoparathyroidism significantly worsens during pregnancy: serum calcium falls, hypocalcemic symptoms may or may not increase, and the doses of supplemental calcium and vitamin D, 1␣-hydroxyvitamin D, or calcitriol have been increased (96,141,148,411,434,510,517,600,669,790,796,821,837,884,936). In one woman the endogenous calcitriol level was low at mid-pregnancy, but measurements in the third trimester were not reported (510).…”
Section: Human Datamentioning
confidence: 49%
“…Indeed, the increased demand of calcium for skeletal mineralization in the last trimester increases the requirement of calcitriol to avoid hypocalcemia. In case reports, oral elemental calcium varies from 800 to 1,500 mg at the beginning of pregnancy to 2,000 to 3,200 mg in the third gestational trimester (C) (142,143). During pregnancy, the daily recommended dose of calcitriol is between 0.25-3 µg.…”
Section: How Should Hypoparathyroidism Be Managed During Pregnancy Anmentioning
confidence: 99%
“…Until now, only limited case reports or case series of pregnant/lactating hypoparathyroid women have been published (1,20,22,24,(29)(30)(31)(32)(33). Among these, the largest case series described 12 cases with HypoPT (20,33), while for women with pseudo-hypoPT, only case reports are available (34)(35)(36)38).…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…Parathyroid hormone (PTH) is essential for calcium homoeostasis, and pregnancy is known for an increased calcium requirement (1). During pregnancy and breastfeeding, physiological changes of maternal calcium metabolism take place to ensure both an adequate fetal skeleton mineralization, with approximately 80% of the mineral accruing in the fetus in the third trimester (9), and a su cient amount of calcium in the breast milk (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation